One-Pot Synthesis of Cyclic Isothioureas - Wang, Jun; Sun, Zhihua (Synlett, 2021)
The one-pot synthesis of cyclic isothioureas is reported. This method provides a straightforward and efficient approach to the synthesis of a broad range of cyclic isothioureas with yields of up to 90% and in quantities of up to 5 g. It is of great value for the preparation of classic organocatalysts, such as benzotetramisole and homobenzotetramisole.
Keywords: cyclic isothioureas; organocatalysts; asymmetric synthesis; bisaminoaryl disulfides